Analysis of fatty acids in Ghee and olive oil and their probable causal effect in lipoid pneumonia (Medical Journal of Indonesia, 2010)
Aim: To analyze and identify the fatty acids found in homemade ghee and in olive oil and compare those to fatty acids found in bronchoalevolar lavage of children with lipoid pneumonia. Methods: The fatty acids found in homemade fat "Ghee" and olive oil were analyzed by gas chromatography. Methyl ester derivatives suitable for GC analysis were prepared directly from olive oil or from Ghee using anhydrous methanolic-HCl. Bronchoscopy and bronchoalevolar lavage was performed in eight children aged between 2 and 4 years, all with history of using homemade ghee and/or olive oil in the recumbent position. Results: The analysis of fatty acids in Ghee and olive oil show similar gas chromatographic pattern as those of bronchoalevolar lavage. Conclusion: The three fatty acids responsible for the deleterious effects of lipoid pneumonia were identified. Lipoid pneumonia should be one of the differentials diagnosis in children presenting with respiratory distress. (Med J Indones 2010; 19:252-7)